Productivity of Full Container Ship and Energy-Economy of its Propulsion Plant - Kos, Serđo (Promet - Traffic&Transportation, 2003)
The paper offers some clear-cut equations and coefficientsexpressing the basic forms of productivity of the container carrierin service: specifically, the productivity of TEU-capacity,the tonnage productivity and transportation efficiency of thecontainer ships. In addition, the power economy of the containership’s propelling plant is being analysed from the viewpointof transportation engineering and an equation is introducedthat enables us to establish the degree of transport economyof the container ship.